Krigsramte bønder. Den demografiske udvikling i et sønderjysk sogn 1620-60 - Perner, Mads L (Historisk Tidsskrift, 2023)
War-stricken Peasants: The Demographic Development in a Schleswig Parish, 1620–1660 As soldiers lived off the land in occupied territories, 17th-century warfare had vast consequences for rural populations. The demographic system was put under pressure as fertility dropped and the transmission of disease led to highly increased mortality. This article studies the long-term demographic consequences of war in Øster Løgum, a parish in the duchy of Schleswig, by attempting to reconstruct the size of its population. It focuses on three periods when foreign troops occupied the duchy: 1627–29, 1644–45 and 1657–60. The study shows that the impact of war varied with regard to mortality: the first and third wars were very deadly to the local population, but the second was not. However, a temporary decrease in fertility was common to all three periods. Further, some major difficulties associated with estimating population sizes across mortality crises are discussed.